Mapping Metacognition: Uncovering Strategic Knowledge in Action - Michelle Yeo; Sarah Hewitt; Joanne Bouma; Rayna Sharma (Journal of the Scholarship of Teaching and Learning)
While concept mapping is widely recognized as an effective active learning strategy, it is still underutilized in higher education. The current literature in SoTL demonstrates the utility of concept maps but the means by which the learning benefits are realized are not well explored. This study focuses on two first year anatomy and physiology courses where nursing students utilized pre-structured concept maps, called skeleton maps, as an assigned weekly study strategy. In this research, we analyzed the skeleton maps collected from participating students for evidence of metacognitive strategies in use. We found five main approaches: the use of diagrams and drawings, color, highlighting, sticky notes (layering), and cross-referencing. Together, these approaches demonstrate elaboration and organizational knowledge, both components of metacognitive strategic knowledge that are at a greater level of sophistication than basic rehearsal. The strategies used by students also demonstrated aspects of the self-knowledge component of metacognition.Rehearsal was the main strategy that students reported pursuing (and the strategy observed by the instructor) prior to the pedagogical change.  Overall, our results show that the skeleton maps significantly shifted the students’ approaches to learning and encouraged metacognitive approaches previously shown to enhance recall and organization of knowledge. This study provides insight into how skeleton maps can support higher level metacognitive learning strategies, providing evidence to encourage their introduction in content-heavy courses.